DUAL EDUCATION AS A MEAN OF ENSURING PROPER QUALITY OF PROFESSIONAL TRAINING OF MATHEMATICS TEACHERS IN MODERN UKRAINE - Микола Працьовитий; Оксана Требенко; Олександр Школьний; Яніна Гончаренко (Фізико-математична освіта)
Formulation of the problem. Qualitative training of teachers, in particular, teachers of mathematics, has always been and is the primary task of a pedagogical university. Currently, in pedagogical universities of Ukraine, master's training takes place in the traditional way, which involves reading lectures, conducting practical, laboratory and seminar classes, as well as practice at school. However, the traditional master's training scheme cannot be adequately provided always, because a significant part of students forced to work at school, and therefore do not attend the required number of lectures and practical classes, and practice at school is reduced to "practicing" it at the workplace. One of the effective ways to solve this problem is to create an effective system of qualitative combination of theoretical and practical training of future teachers with professional activities even during their studies at the university.